Assessing variability in audiovisual speech integration skills using capacity and accuracy measures. (October 2014) - Altieri, Nicholas; Hudock, Daniel
Abstract Objective: While most normal-hearing listeners rely on the auditory modality to obtain speech information, research has demonstrated the importance that non-auditory modalities have on language recognition during face-to-face communication. The efficient utilization of the visual modality becomes increasingly important in difficult listening conditions, and especially for older and hearing-impaired listeners with sensory or cognitive decline. First, this report will quantify audiovisual integration skills using a recently developed capacity measure that incorporates speed and accuracy. Second, to investigate sensory factors contributing to integration ability, high and low-frequency hearing thresholds will be correlated with capacity, as well as gain measures from sentence recognition. Design: Integration scores were obtained from a within-subjects design using an open-set sentence speech recognition experiment and a closed set speeded-word classification experiment, designed to examine integration (i.e. capacity). Study sample: A sample of 44 adult listeners without a self-reported history of hearing-loss was recruited. Results: Results demonstrated a significant relationship between measures of audiovisual integration and hearing thresholds. Conclusions: Our data indicated that a listener's ability to integrate auditory and visual speech information in the domains of speed and accuracy is associated with auditory sensory capabilities and possibly other sensory and cognitive factors.